Microbial quality of edible grasshoppers Ruspolia differens (Orthoptera: Tettigoniidae): From wild harvesting to fork in the Kagera Region, Tanzania. Issue 1 (23rd November 2018) - Ng'ang'a, Jeremiah; Imathiu, Samuel; Fombong, Forkwa; Ayieko, Monica; Vanden Broeck, Jozef; Kinyuru, John
Abstract: In Tanzania, edible Ruspolia differens are still harvested from the natural environments. In this perspective, little is known about the microbiological quality of wild harvested R. differens . This study was conducted to assess the microbiological quality of wild harvested R. differens and evaluate the efficacy of conventional processing methods in reducing microbial load. Two districts (Bukoba rural and Muleba) within the Kagera region were purposively selected for the study. Sampling was done from the same batches along the R. differens food chain as follows: (a) at harvest points in the villages, (b) after transportation to the market and plucking of wings and legs, (c) after rinsing with potable tap water, and (d) after processing using conventional methods. Generally, high microbial counts, that is, total viable aerobic count (TVC), Enterobacteriaceae, lactic acid bacteria, bacterial endospores, and yeasts and molds were observed in raw R. differens samples. A significant increase in microbial counts after transportation and plucking was only observed for TVC, bacterial endospores, and yeasts and molds. A statistically significant reduction in all types of counts, with the exception of bacterial endospores, was observed after processing. All processed samples analyzed were devoid of salmonellae, Listeria monocytogenes, and Escherichia coli . Practical applications: Although commonly used processing methods of Ruspolia differens were effective in reducing microbial load, bacterial endospores were hardly eliminated and could pose a health hazard to consumers; thus, improved handling of R. differens along the food chain could reduce such risks.